Integrating Psychological Configurations in Teacher Education: A Competency Framework for Pedagogy-Psychology Students - Maryen Cabrera; Yaneisy Martínez; Camilo Díaz (Universitas Majalengka, 2025)
Background: Contemporary educational contexts demand that Pedagogy-Psychology professionals possess integrated competencies beyond traditional skill-based training. Cuban undergraduate programs face challenges in aligning curriculum with complex socio-educational demands requiring holistic professional preparation. Objective: This study proposes and validates a competency-based framework for undergraduate Pedagogy-Psychology students in Cuba, addressing gaps in initial teacher education for psychology-pedagogy professionals. Methods: Employing a dialectical-materialist approach, this qualitative study utilized analysis-synthesis, inductive-deductive, and holistic-configurational methods to develop the competency framework. Expert consultation with 27 specialists from a scientific research project validated the framework's feasibility through structured evaluation criteria assessing theoretical conception, contextual correlation, and structural argumentation. Results: The framework comprises three specific professional competencies (psycho-pedagogical advisory, guidance, and didactic), four basic professional competencies (teamwork, conflict resolution, research, and digital), and one transversal competency (communicative). Expert validation demonstrated strong feasibility (85.19%) and contextual relevance (92.59%), confirming viability for transforming skill-based approaches. Conclusion: The validated framework advances competency-based education theory by specifying how professional competencies develop as complex psychological configurations integrating motivational, cognitive, and personal resources. It provides actionable guidance for Cuban curriculum redesign while offering international applicability for developing countries pursuing teacher education reform.